Dietary fibre linked to decreased inflammation in overweight minority youth. Issue 1 (2nd March 2015) - Miller, S. J.; Batra, A. K.; Shearrer, G. E; House, B. T.; Cook, L. T.; Pont, S. J.; Goran, M. I.; Davis, J. N.
Summary: Objective: The objective of this study was to examine the relationship between diet and inflammation, and adiposity in minority youth. Design and Methods: The study was designed as a cross‐sectional analysis of 142 overweight (≥85th body mass index percentile) Hispanic and African–American adolescents (14–18 years) with the following measures: anthropometrics, adiposity via magnetic resonance imaging, dietary intake via 24‐h dietary recalls, and inflammation markers from fasting blood draws utilizing a multiplex panel. Partial correlations were estimated and analysis of covariance (ancova ) models fit to examine the relationship among dietary variables, inflammation markers and adiposity measures with the following a priori covariates: Tanner stage, ethnicity, sex, total energy intake, total body fat and total lean mass. Results: Inference based onancova models showed that the highest tertile of fibre intake (mean intake of 21.3 ± 6.1 g d −1 ) vs. the lowest tertile of fibre intake (mean intake of 7.4 ± 1.8 g d −1 ) was associated with 36% lower plasminogen activator inhibitor‐1 ( P = 0.02) and 43% lower resistin ( P = 0.02), independent of covariates. Similar results were seen for insoluble fibre. No other dietary variables included in this study were associated with inflammation markers. Conclusions: These results suggest that increases in dietary fibre could play an important role in lowering inflammation and therefore metabolic disease risk in high‐risk minority youth.